104k views
1 vote
Simplify so that your answer contains only positive exponents.​

Simplify so that your answer contains only positive exponents.​-example-1

1 Answer

5 votes

Explanation:

18.


= { ({x}^(2)) }^( - 3) .2 {x}^(3)


= {x}^(2 * ( - 3)) .2 {x}^(3)


= {x}^( - 6) .2 {x}^(3)


= 2 {x}^( - 6 + 3)


= 2 {x}^(3)


= \frac{2}{ {x}^(3) }


\:

19.


= {(2m)}^(2) . {(3 {m}^(3) )}^(2)


= {2}^(2) {m}^(2) . {3}^(2) {m}^(3 * 2)


= 4 {m}^(2) .9 {m}^(6)


= (4 * 9) {m}^(2 + 6)


= 36 {m}^(8)

User Leonardorame
by
5.0k points